Celebrate the feasts of the Old Testament in your own home or church - Zimmerman, Martha, 1934- (Bethany Fellowship, 1981)
The great religious feasts as described in the Old Testament and Jewish tradition are full of spiritual truth presented in the New Testament, especially as they recreate the symbolic representations of Christ. When those festivals are re-enacted in the Christian home, children have a living picture of Bible principles as exemplified in and through Jesus, the prophesied Messiah. They learn far better by experience than by only hearing. Every Christian family can benefit from understanding the Jewish roots of their faith without becoming enslaved to Jewish traditions